Recurrent and de novo Glomerulonephritis After Kidney Transplantation - Lim, Wai H.; Shingde, Meena; Wong, Germaine (Frontiers in Immunology, 2019)
The prevalence, pathogenesis, predictors and natural course of patients with recurrent glomerulonephritis (GN) occurring after kidney transplantation remains incompletely understood, including whether there are differences in the outcomes and advances in the treatment options of specific GN subtypes, including those with de novo GN. Consequently, the treatment options and approaches to recurrent disease are largely extrapolated from the general population, with responses to these treatments in those with recurrent or de novo GN post-transplantation poorly described. Given a greater understanding of the pathogenesis of GN and the development of novel treatment options, it is conceivable that these advances will result in an improved structure in the future management of patients with recurrent or de novo GN. This review focuses on the incidence, genetics, characteristics, clinical course and risk of allograft failure of patients with recurrent or de novo GN after kidney transplantation, ascertaining potential disparities between “high risk” disease subtypes of IgA nephropathy, idiopathic membranous glomerulonephritis, focal segmental glomerulosclerosis and membranoproliferative glomerulonephritis. We will examine in detail the management of patients with high risk GN, including the pre-transplant assessment, post-transplant monitoring and the available treatment options for disease recurrence. Given the relative paucity of data of patients with recurrent and de novo GN after kidney transplantation, a global effort in collecting comprehensive in-depth data of patients with recurrent and de novo GN as well as novel trial design to test the efficacy of specific treatment strategy in large scale multicentre randomised controlled trials are essential to address the knowledge deficiency in this disease.